المضامين التربوية المستنبطة من سورة العصر وآثارها - العمودي، وليد محمد حسن Alamoudi, Walid Mohamed Hassan (عبد الفتاح محمود ادريس, 2018)
This study is entitled: (The Educational Contents Derived from Surat Al-Asr, and its Effects) The study defines: Educational contents, values, principles, devising, both linguistically and terminologically. Then it provides general information about Sura Al-Asr, which includes the following: naming the Sura, its merits, the number of its verses, its place of revelation, type, subjects, purposes, main objective, and its harmony with the preceding and following chapters. The study also explains the principle of education to achieve the pillars of faith through the Sura. The study shows the value of good work, its importance, the conditions of its acceptance by Allah, and its educational effects. The study then shows the value of steadfastness on the right path and patience, the importance of doing righteous deeds, and joining together in the mutual teaching of truth, and of patience. The study also explains the types of patience, its degrees, importance, and the educational effects of joining together in the mutual teaching of truth, and of patience.
تناولت هذه الدراسة التي بعنوان: (المضامين التربوية المستنبطة من سورة العصر، وأثارها)، وتعريف كل من: المضامين التربوية، والقيم، والمبادئ، والاستنباط، لغة واصطلاحا، والتعريف بسورة العصر تعريفا عاما، اشتمل على ما يلي: تسمية السورة، وفضلها، وعدد آياتها، ومكان نزولها، ونوعها، وموضوعاتها، وهدفها ومقصدها الرئيس، ومناسبتها لما قبلها ولما بعدها، وشرحت مبدأ التربية على تحقيق أركان الإيمان من خلال السورة، وأظهرت الدراسة قيمة العمل الصالح، وأهميته، وشروط قبوله عند الله عز وجل، وآثاره التربوية، ثم بينت قيمة الثبات على الحق والصبر عليه، وأهمية التواصي بالحق والتواصي بالصبر، كما بينت أنواع الصبر، ودرجاته، وأهميته، والآثار التربوية لخلق التواصي بالحق والتواصي بالصبر.
Keywords: القرآن الكريم -- سورة العصر -- المضامين التربوية -- فضائل السور -- الأخلاق الإسلامية